Global damage indexes for the seismic performance assessement of RC structures. - Scotta, Roberto (Earthquake engineering & structural dynamics.)
When performing the seismic risk assessment of new or existing buildings, the definition of compact indexes able to measure the damaging and safety level of structures is essential, also in view of the economic considerations on buildings rehabilitation. This paper proposes two series of indexes, named, respectively, Global Damage Indexes (GDIs), which are representative of the overall structure performance, and Section Damage Indexes (SDIs), which assess the conditions of reinforced concrete (RC) beam-column sections. Such indexes are evaluated by means of an efficient numerical model able to perform nonlinear analyses of the RC frame, based on the continuum damage mechanics theory and fiber approach. An improvement of a two-parameter damage model for concrete, developed by some of the authors, which guarantees a better correlation between the Local Damage Indexes (LDIs) and the material's mechanical characteristics, is also presented. For the reinforcement, a specific LDI, named ?steel damage index?, which takes into account the plastic strain development and the bar buckling effect, is proposed. The numerical model has been employed to simulate several experimental tests, in order to verify the accuracy of the proposed approach in predicting the RC member's behavior. Nonlinear static and dynamic analyses of two RC frames are carried out. The robustness of the method, as well as the effectiveness of the GDIs in assessing the structural conditions, are demonstrated here. Finally, comparisons between the evolution of GDIs and the achievement of the performance levels as proposed in FEMA 356 are reported.